1985
DOI: 10.1111/j.1570-7458.1985.tb03547.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fecundity and oocyte resorption in field populations of Lucilia cuprina

Abstract: In the Australian sheep blowfly, Lucilia cuprina, the number of ovarioles, and hence the maximum number of eggs developed in each ovarian cycle, is a linear function of adult size (headwidth). Field females have a mean headwidth of 3.0 mm (range=2.30–3.50 mm) and a mean potential fecundity/cycle of 232 eggs (range=111–318 eggs). Realised fecundity is influenced by the quality and amount of protein in the adult diet. All field females appear to have the same minimum protein requirement for egg maturation, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…Similar results of small-sized flies resulting from underfed larvae being able to lay eggs were reported in L. cuprina by Webber (1955). The latter study also demonstrated that their fecundity was reduced as the numbers of functional ovarioles, and hence the maximum number of eggs developed in each ovarian cycle, is a linear function of adult size (Mackerras, 1933;Webber, 1955;Foster, et al, 1975, Vogt et al, 1985.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results of small-sized flies resulting from underfed larvae being able to lay eggs were reported in L. cuprina by Webber (1955). The latter study also demonstrated that their fecundity was reduced as the numbers of functional ovarioles, and hence the maximum number of eggs developed in each ovarian cycle, is a linear function of adult size (Mackerras, 1933;Webber, 1955;Foster, et al, 1975, Vogt et al, 1985.…”
Section: Discussionsupporting
confidence: 80%
“…These larvae are either dying or are being resorbed, more than probably as a result of a lack of sufficient protein sources and/or suitable larviposition sites. There is evidence in the field of delays in the location of suitable oviposition sites in female Lucilia cuprina (Diptera: Calliphoridae) (Vogt et al , 1985a). How long after larval development is complete this process commences is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of livestock, mainly cattle, plays a very important role in the management of the dehesa ecosystem. Although carrion represents the natural source of high quality protein in the field, faeces of grazing animals are also believed to be an important source of protein for egg maturation ( Vogt et al . 1985b ; Stoffolano et al .…”
Section: Discussionmentioning
confidence: 99%